BUILDING SMART CITY IN HO CHI MINH CITY WITH MODERN DIGITAL TECHNOLOGY - Thong, Lương Nguyễn Duy; Huy, Đặng Xuân; Khanh, Nguyễn Trọng (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Building a civilized city associated with modern digital technologies is becoming a necessity for major cities in the world. In Vietnam, Ho Chi Minh City is a typical example of prioritizing the development of civilization associated with modern digital technology. The article presents three main issues: (1) An overview of digital technology and smart cities, (2) Presenting the urban reality of Ho Chi Minh City for smart city development, (3) Develop a number of solutions to build a civilized Ho Chi Minh City in the direction of a smart city.